Pengaruh Tingkat Produksi, Harga dan Konsumsi Terhadap Impor Bawang Merah di Indonesia - Dewi, Mayun Karina; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
Agriculture horticulture, especially the onion is one of the strategic sectors are being developed by the government. As one of the countries with the largest number of people who occupied the fifth position in the world that have an impact on national food needs are high, but Indonesia has not been able to meet domestic food needs special onion. This study aims to determine the effect of production, price, consumption, against imports of onions simultaneously and partially. In addition, this study aims to determine the dominant variable affecting the import of garlic in Indonesia. The data used in this study is a secondary data analysis method used is multiple linear regression analysis. The analysis showed the simultaneous production levels, prices and consumption affect the import of onion in Indonesia. Partially significant negative effect on the level of production, on the other hand consumption and prices were found to have a significantly positive nd on onion imports in Indonesia. In this analysis shows that the variable dominant influence on the import of garlic consumption in Indonesia is variable .
Keywords: Import of onion, production levels, prices, consumption